Nickel-based superalloy for additive manufacturing, additive manufacturing method of nickel-based superalloy and additive manufacturing part

By adjusting the composition and process of nickel-based high-temperature alloys, a γ' phase with high Al and low Ti is formed, which solves the problem that nickel-based high-temperature alloys are prone to cracks in additive manufacturing, improves the high-temperature performance and density of the alloy, and meets the high-temperature Parts use requirements.

CN119464844APending Publication Date: 2025-02-18SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411596246.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In additive manufacturing, nickel-based high-temperature alloys are prone to cracks during the laser melting of selected areas, resulting in insufficient density and high-temperature performance, and cannot meet the requirements of parts with temperatures above 900℃.

Method used

By adjusting the alloy composition, the content of elements such as Co, Cr, Al, Ta, Nb, Re is increased, and the γ' phase with high Al and low Ti is formed, which improves the high temperature stability and printability of the alloy, and is also smelting and plasma through vacuum induction. Powder is prepared by rotary electrode atomization method and 3D printing is carried out in combination with SLM technology.

Benefits of technology

It significantly reduces the crack sensitivity of the alloy during the SLM process, improves the density and high-temperature performance of additive manufacturing parts, and meets the requirements of hot-end components of aero engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464844A_ABST
    Figure CN119464844A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of additive manufacturing, in particular to a nickel-based high-temperature alloy for additive manufacturing, an additive manufacturing method of the nickel-based high-temperature alloy and an additive manufacturing part. The nickel-based high-temperature alloy comprises 17.2%-23.4% of Co, 7.2%-10.5% of Cr, 5.4%-6.1% of Al, 0.01%-0.1% of Ti, 1.5%-2% of Mo, 2%-4% of W, 6.1%-8.1% of Ta, 0.5%-1% of Nb, 0.5%-3.1% of Re, 0.02%-0.1% of Si, 0.13%-0.2% of C, 0.005%-0.01% of B, less than or equal to 0.2% of Hf, less than or equal to 0.01% of Zr and the balance Ni. The printability of the alloy is improved by controlling the variety and content of key alloy elements in the alloy, and the high-temperature performance of the alloy is improved through high Al, low Ti and a proper amount of Ta, Nb, Re and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a nickel-based high-temperature alloy for additive manufacturing, an additive manufacturing method thereof, and an additive manufactured part. Background Art

[0002] High-temperature alloys have excellent mechanical properties and good oxidation resistance and corrosion resistance. They are key materials for the preparation of hot-end components of aerospace and aviation power systems. With the continuous development of the aerospace and aviation industries, the design requirements of core components have gradually increased. More complex internal flow channels and thin-walled structures have appeared inside the parts, and traditional casting, forging and welding processes can no longer meet the design requirements. Selective laser melting (SLM) has the characteristics of high forming efficiency and the ability to prepare complex structural parts. It has become the preferred technical solution for the preparation of complex structural parts of high-temperature alloys. At present, most of the high-temperature alloys used in additive manufacturing are designed for traditional processing methods, such as investment casting, forging and welding. Therefore, defects generated during additive manufacturing, especially cracks, are still one of the main challenges for SLM forming nickel-based high-temperature alloys. Only a few nickel-based high-temperature alloys can be prepared with high density within a relatively wide range of processing parameters, but there are still problems such as insufficient temperature resistance and low high-temperature mechanical properties, and they cannot be used for parts with a service temperature above 900°C.

[0003] Since the forming process of additive manufacturing technology is completely different from traditional processes, existing high-performance high-temperature alloys are very prone to defects such as microcracks and holes when using additive manufacturing technology to prepare parts, which seriously restricts the application of additive manufacturing technology in key high-temperature components.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a nickel-based high-temperature alloy for additive manufacturing, which has low crack sensitivity during the SLM process and can ensure both the density and high-temperature performance of additively manufactured components.

[0006] Another object of the present invention is to provide an additive manufacturing method for the above-mentioned nickel-based high-temperature alloy for additive manufacturing.

[0007] Another object of the present invention is to provide an additively manufactured part made of the above-mentioned nickel-based high-temperature alloy for additive manufacturing.

[0008] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a nickel-based high-temperature alloy for additive manufacturing, comprising the following components in mass percentage:

[0009] Co 17.2%~23.4%, Cr 7.2%~10.5%, Al 5.4%~6.1%, Ti 0.01%~0.1%, Mo 1.5%~2%, W 2%~4%, Ta 6.1%~8.1%, Nb 0.5%~1%, Re 0.5%~3.1%, Si0.02%~0.1%, C 0.13%~0.2%, B 0.005%~0.01%, Hf≤0.2%, Zr≤0.01%, and the balance is Ni and unavoidable impurities.

[0010] In a specific embodiment of the present invention, in the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is ≤6.1%. Further, in the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is 5.6% to 6.1%.

[0011] In a specific embodiment of the present invention, in the nickel-based high-temperature alloy for additive manufacturing, the mass percentage of Hf is 0.04% to 0.12%.

[0012] In a specific embodiment of the present invention, in the nickel-based high-temperature alloy for additive manufacturing, the mass percentage of Zr is 0.001% to 0.01%.

[0013] The second aspect of the present invention provides a method for preparing the nickel-based high-temperature alloy for additive manufacturing according to the first aspect, comprising the following steps:

[0014] According to the ingredients of the nickel-based high-temperature alloy for additive manufacturing, a master alloy ingot is obtained by vacuum induction melting, and then the powder of the nickel-based high-temperature alloy for additive manufacturing is obtained by vacuum gas atomization or plasma rotating electrode atomization.

[0015] The third aspect of the present invention provides an additive manufacturing method of the nickel-based high-temperature alloy for additive manufacturing according to the first aspect, comprising the following steps:

[0016] 3D printing of nickel-based high-temperature alloy powder for additive manufacturing under protective atmosphere;

[0017] In the 3D printing, the laser power is 250-300W, and the scanning speed is 700-1000mm / s.

[0018] In a specific embodiment of the present invention, in the 3D printing, the laser power is 270-280 W, and the scanning speed is 800-900 mm / s.

[0019] In a specific embodiment of the present invention, in the 3D printing, the spot diameter is 0.08-0.12 mm.

[0020] In a specific embodiment of the present invention, in the 3D printing, the scanning interval is 0.08 to 0.12 mm.

[0021] In a specific embodiment of the present invention, in the 3D printing, the thickness of a single layer of powder is 0.025 to 0.035 mm.

[0022] In a specific embodiment of the present invention, the particle size of the nickel-based high-temperature alloy powder for additive manufacturing is 15 to 53 μm.

[0023] Another aspect of the present invention provides an additively manufactured part, which is manufactured using the additive manufacturing method of the nickel-based high-temperature alloy for additive manufacturing described in the third aspect.

[0024] In a specific embodiment of the present invention, the density of the additively manufactured part is ≥99.7%.

[0025] In a specific embodiment of the present invention, the room temperature tensile strength of the additively manufactured part is ≥1340MPa, preferably ≥1400MPa, and the room temperature elongation after break is ≥9%, preferably ≥11.2%; the 1100°C tensile strength of the additively manufactured part is ≥180MPa, preferably ≥199MPa, and the elongation after break at 1100°C is ≥7%, preferably ≥9%; the fracture time in the 1000°C / 150MPa high temperature endurance test is ≥17.3h, preferably ≥30h, and the elongation after break is ≥7.8%, preferably ≥10.1%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention improves the printability of the alloy by controlling the types and contents of key alloying elements in the alloy composition, and improves the high temperature stability of γ' and the high temperature performance of the alloy by using high Al, low Ti and appropriate amounts of Ta, Nb, Re, etc.;

[0028] (2) The present invention regulates the additive manufacturing process of the nickel-based high-temperature alloy according to its composition; the additive manufacturing process of the present invention can be used to manufacture hot-end components of aircraft engines with complex structures and can meet the requirements of hot-end components of aircraft engines. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1The optical microstructure diagram of the printed sample provided in Example 1 of the present invention;

[0031] Figure 2 The optical microstructure diagram of the printed sample provided in Example 2 of the present invention;

[0032] Figure 3 The optical microstructure diagram of the printed sample provided in Example 3 of the present invention;

[0033] Figure 4 The optical microstructure diagram of each printed sample provided by the fourth group of embodiments of the present invention;

[0034] Figure 5 The optical microstructure diagram of the printed sample provided for Comparative Example 1;

[0035] Figure 6 The optical microstructure diagram of the printed sample provided for Comparative Example 2;

[0036] Figure 7 The optical microstructure diagram of the printed sample provided for Comparative Example 3;

[0037] Figure 8 The optical microstructure diagram of the printed sample provided for Comparative Example 4;

[0038] Fig. 9 The optical microstructure diagram of the printed sample provided for Comparative Example 5;

[0039] Fig.10 The optical microstructure diagram of the printed sample provided for Comparative Example 6;

[0040] Fig.11 This is an optical microstructure image of the printed sample provided for Comparative Example 7. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0042] In order to meet the requirements of high temperature and high strength of key hot parts in aerospace engines, and to address the problem that existing alloy powders are prone to cracking during additive manufacturing, the first aspect of the present invention provides a nickel-based high-temperature alloy for additive manufacturing, comprising the following components by mass percentage:

[0043] Co 17.2%~23.4%, Cr 7.2%~10.5%, Al 5.4%~6.1%, Ti 0.01%~0.1%, Mo 1.5%~2%, W 2%~4%, Ta 6.1%~8.1%, Nb 0.5%~1%, Re 0.5%~3.1%, Si0.02%~0.1%, C 0.13%~0.2%, B 0.005%~0.01%, Hf≤0.2%, Zr≤0.01%, and the balance is Ni and unavoidable impurities.

[0044] The present invention improves the printability of the alloy by controlling the types and contents of key alloy elements in the alloy composition, and forms a γ' phase through a combination of high Al and low Ti. The γ'-Ni3Al has better stability. At the same time, appropriate amounts of Ta, Nb, etc. are added to increase the content of the γ' phase of the alloy, thereby improving the high-temperature performance of the alloy.

[0045] The present invention achieves the effect by compounding various elements in proportion and synergizing various elements. The alloy composition characteristics of the present invention are as follows.

[0046] In the alloy of the present invention, the Co element can be completely soluble in the matrix Ni, can expand the γ phase region, and play a role in solid solution strengthening in the alloy. Co can also reduce the stacking fault energy of the alloy matrix, improve the medium temperature performance of the alloy, and improve the alloy forming performance and organizational stability; the increase in the Co content can improve the weldability of the alloy, but too high a Co content will reduce the solid solution temperature, resulting in a decrease in the high temperature performance of the alloy. In order to ensure the high temperature performance of the alloy, in the alloy of the present invention, the mass percentage of Co is regulated to be 17.2% to 23.4%. For example, in different embodiments, the mass percentage of Co can be 17.2%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.4% or a range consisting of any two of them.

[0047] The Cr element has the effect of solid solution strengthening in nickel-based high-temperature alloys, and forms an oxide layer on the metal surface at high temperatures to improve the alloy's oxidation resistance. However, studies have found that in the alloy of the present invention, excessive Cr content will promote the precipitation of harmful secondary phases, increase the tendency of component cracking, and affect the high-temperature mechanical properties of the alloy. In the alloy of the present invention, regulating the mass percentage of Cr to 7.2% to 10.5% is more helpful to avoid cracking and ensure the performance of the alloy. For example, in different embodiments, the mass percentage of Cr can be 7.2%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, or a range consisting of any two of them.

[0048] The Al element is one of the γ′ phase-forming elements, which can increase the dissolution temperature and stability of the γ′ phase, and can significantly increase the volume fraction of the γ′ phase. Compared with the γ′ formed by the Ti element, the γ′ formed by the Al element has better high-temperature stability, that is, Ni3Al has better stability. In addition, Al can form a dense oxide film at high temperatures to improve the oxidation resistance of the alloy, but if the Al content is too high, it will promote the formation of low-melting-point γ / γ′ eutectic between dendrites, which is not conducive to the forming of the alloy in the additive manufacturing process. Therefore, in the alloy of the present invention, the mass percentage of Al is regulated to be 5.4% to 6.1%. For example, in different embodiments, the mass percentage of Al can be 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1% or a range composed of any two of them.

[0049] Ti is one of the γ′ phase-forming elements and a carbide-forming element, which can promote the performance of MC carbides. However, the increase in carbides and their growth after post-treatment will affect the high-temperature performance of the alloy. In addition, the γ′ phase formed by Ti has poor high-temperature stability. The increase in Ti content will also reduce the solidus temperature and increase the γ′ phase coarsening rate, and promote the formation of low-melting γ / γ′ eutectic between dendrites. Therefore, in the alloy of the present invention, the mass fraction of Ti is regulated in the range of 0.01% to 0.1%, so as to take into account the mechanical properties and high-temperature stability of the alloy. For example, in different embodiments, the mass fraction of Ti in the present invention can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or a range consisting of any two of them.

[0050] In the alloy of the present invention, the Mo element is concentrated in the matrix and is a solid solution strengthening element, which is beneficial to the alloy's forming properties and mechanical properties. However, too high a Mo content will promote the precipitation of TCP harmful phases. The present invention regulates the mass percentage of Mo to 1.5% to 2% to take into account both forming properties and mechanical properties. For example, in different embodiments, the mass percentage of Mo in the present invention can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or a range consisting of any two of them.

[0051] In the alloy of the present invention, the W element dissolves both in the γ matrix and in the γ ′ In the phase, it can increase the dissolution temperature and stability of the γ′ phase, increase the volume fraction of the γ′ phase, and has a significant solid solution strengthening effect, and can control the coarsening rate of the γ′ phase. However, excessive W elements will promote the formation of the TCP phase. The present invention regulates the mass fraction of W to be 2% to 4%. For example, in different embodiments, the mass fraction of W can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4% or a range consisting of any two of them.

[0052] In the alloy of the present invention, the Ta element tends to segregate in the γ′ phase, significantly improving the dissolution temperature and stability of the γ′ phase, and can enhance the high-temperature mechanical properties of the alloy. However, too high a Ta content will promote the precipitation of harmful secondary phases and increase the tendency of the workpiece to crack. The present invention regulates the mass percentage of Ta to 6.1% to 8.1%, which is more conducive to taking into account both high-temperature mechanical properties and avoiding cracking problems. For example, in different embodiments, the mass percentage of Ta can be 6.1%, 6.2%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.8%, 8%, 8.1% or a range consisting of any two of them.

[0053] The Nb element is a γ′ phase-forming element, which can increase the dissolution temperature of the γ′ phase and enhance the high-temperature mechanical properties of the alloy. However, too high a Nb content will promote the precipitation of harmful phases in TCP. The present invention adjusts the mass percentage of Nb to 0.5% to 1%, and cooperates with the other components to better balance high-temperature mechanical properties and avoid the problem of harmful phase precipitation. For example, in different embodiments, the mass percentage of Nb can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of them.

[0054] In the alloy of the present invention, the Re element mainly enters the γ matrix to form a short-range ordered Re atomic group with a size of about 1 nm. Compared with the solute atoms that are independent of each other in the solid solution state, the atomic group reduces the diffusion rate of the alloying elements, effectively hinders the movement of dislocations, prevents the coarsening of the γ' strengthening phase, and increases the mismatch of γ / γ'. The appropriate addition of the Re element will improve the high temperature stability of the γ' strengthening phase. However, due to the large size of the Re atoms, excessive use will produce too many low-melting eutectic phases at the grain boundaries, resulting in cracks and affecting the printability of the alloy. Therefore, in the alloy of the present invention, the mass fraction of Re is regulated to be 0.5% to 3.1%, which can improve the high temperature performance of the alloy while ensuring the printability of the alloy. For example, in different embodiments, the mass fraction of Re can be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 2.8%, 3.1% or a range composed of any two of them.

[0055] The addition of Si element is beneficial to improve the oxidation resistance of the alloy, but too high Si content will reduce the mechanical properties of the alloy, and the content of Si needs to be strictly limited. In the alloy of the present invention, the mass percentage of Si is 0.02% to 0.1%, such as 0.02%, 0.04%, 0.05%, 0.08%, 0.1% or any two thereof.

[0056] The C element is a grain boundary strengthening element, which is beneficial to deoxidation and improves the purity of the alloy during the alloy smelting process. In the process of additive manufacturing, dispersed carbides can be formed at the grain boundaries to improve the mechanical properties, and the appropriate increase in the C content can reduce the solidification temperature range of the alloy, reduce the formation of cracks such as solidification cracks, and improve the printability of the alloy to a certain extent. However, too high a C content will cause continuous carbides to precipitate at the grain boundaries, which is not conducive to the mechanical properties of the alloy. For example, in different embodiments, in the alloy of the present invention, the mass fraction of C can be 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% or a range consisting of any two of them.

[0057] The B element is a grain boundary strengthening element that increases the plasticity of the alloy and is beneficial to the coordinated deformation of the grain boundaries during additive manufacturing. However, a large amount of borides formed by excessive B content is not conducive to the mechanical properties of the alloy, nor is it conducive to the printing of the alloy. Therefore, the present invention regulates the mass fraction of B to be below 0.01%. For example, in different embodiments, the mass fraction of B can be 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.015, or a range consisting of any two of them.

[0058] The Hf element is a strong γ′-forming element in the casting alloy, which can strengthen the γ′ phase and purify the free S at the grain boundary or between dendrites to improve the bonding strength of these weak parts, thereby delaying the formation and expansion of cracks. However, if the Hf content is too high during the additive manufacturing process, it will reduce the initial melting temperature of the alloy, form a low melting point phase, form an Hf-rich liquid film, and promote the formation of cracks. Therefore, Hf is added to the alloy of the present invention, and the mass fraction of Hf is preferably controlled to be 0.04% to 0.12%. For example, in different embodiments, the mass fraction of Hf can be 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, or a range consisting of any two of them.

[0059] The Zr element is a grain boundary strengthening element that can purify the grain boundaries and improve the plasticity of the alloy. However, too high a Zr content will lower the solidus temperature, expand the solidification temperature range, and is not conducive to the printing of the alloy. Therefore, Zr is added to the alloy of the present invention, and the mass fraction of Zr is controlled to be less than 0.01%, preferably 0.001% to 0.01%. For example, in different embodiments, the mass fraction of Zr can be 0.001%, 0.002%, 0.004%, 0.005%, 0.006%, 0.008%, 0.01% or a range consisting of any two of them.

[0060] In a specific embodiment of the present invention, in the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is ≤6.1%. Further, in the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is 5.6% to 6.1%.

[0061] Too high an amount of Al and Ti elements will affect the printing performance of the alloy. The present invention regulates the amount of Al and Ti within the above range, and cooperates with other components to help improve the printing performance and high temperature performance of the alloy. For example, in different embodiments, the sum of the mass percentages of Al and Ti can be 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1% or a range consisting of any two of them.

[0062] The second aspect of the present invention provides a method for preparing the nickel-based high-temperature alloy for additive manufacturing provided in the first aspect, comprising the following steps:

[0063] According to the ingredients of the nickel-based high-temperature alloy for additive manufacturing, a master alloy ingot is obtained by vacuum induction melting, and then the powder of the nickel-based high-temperature alloy for additive manufacturing is obtained by vacuum gas atomization or plasma rotating electrode atomization.

[0064] Among them, vacuum induction melting, vacuum gas atomization, and plasma rotating electrode atomization can be carried out according to conventional processes. As long as spherical powders with a particle size of 15 to 53 μm, a D10 range of 26 to 28 μm, a D90 range of 53 to 55 μm, and an oxygen content of ≤100 ppm can be obtained, the specific parameters are not described here.

[0065] The third aspect of the present invention provides an additive manufacturing method of the nickel-based high-temperature alloy for additive manufacturing provided in the first aspect, comprising the following steps:

[0066] 3D printing of nickel-based high-temperature alloy powder for additive manufacturing under protective atmosphere;

[0067] In 3D printing, the laser power is 250-300W and the scanning speed is 700-1000mm / s.

[0068] In actual operation, the protective atmosphere may be an argon atmosphere, and the purity of the argon may be above 99.99%. In addition, the oxygen content in the forming chamber is below 0.1%.

[0069] For example, in different embodiments, the laser power can be 250W, 260W, 270W, 280W, 290W, 300W or a range consisting of any two thereof; the scanning speed can be 700mm / s, 750mm / s, 800mm / s, 850mm / s, 900mm / s, 950mm / s, 1000mm / s or a range consisting of any two thereof.

[0070] When the laser power is too low, the metal powder is not fully melted, the viscosity of the micro-melting pool is too large, and sintering is likely to occur between the powder particles, which reduces the metallurgical bonding between the layers and causes the density of the molded part to be low. When the laser power is too large, it is easy to cause the molding surface to be uneven, resulting in a decrease in the density of the molded part. When the scanning speed is low, the volume of the liquid phase formed is large, and the liquid column is unstable, which will cause the thickness of the next layer of powder to be uneven, thereby causing the density to decrease; at the same time, the volume of the molten pool is large, which will inhale the unmelted powder particles near the molten pool, causing the powder particles to exist in a semi-molten state, and finally leading to the formation of holes, which reduces the density of the molded part. When the scanning speed exceeds a certain critical value, the amount of melted powder is too small, so that the overlap rate of adjacent melt channels is too low, the melt channels are not easy to keep straight, and are prone to bending and intermittent phenomena, and cannot form a good metallurgical bond. The present invention regulates the process parameters of 3D printing for the alloy of the present invention, and can take into account the performance and processability of 3D printed parts.

[0071] In a specific embodiment of the present invention, in 3D printing, the laser power is 270-280 W, and the scanning speed is 800-900 mm / s.

[0072] In a specific embodiment of the present invention, in 3D printing, the spot diameter is 0.08-0.12 mm.

[0073] For example, in different embodiments, in 3D printing, the spot diameter may be 0.08 mm, 0.09 mm, 0.1 mm, 0.11 mm, 0.12 mm, or a range consisting of any two of them.

[0074] In a specific embodiment of the present invention, in 3D printing, the scanning interval is 0.08 to 0.12 mm.

[0075] For example, in different implementations, in 3D printing, the scanning pitch may be 0.08 mm, 0.09 mm, 0.1 mm, 0.11 mm, 0.12 mm, or a range consisting of any two of these.

[0076] In a specific embodiment of the present invention, in 3D printing, the thickness of a single layer of powder is 0.025 to 0.035 mm.

[0077] For example, in different embodiments, in 3D printing, the thickness of a single layer of powder can be 0.025 mm, 0.026 mm, 0.028 mm, 0.03 mm, 0.032 mm, 0.034 mm, 0.035 mm, or a range consisting of any two of them.

[0078] In a specific embodiment of the present invention, the particle size of the nickel-based high-temperature alloy powder for additive manufacturing is 15 to 53 μm.

[0079] In actual operation, after powdering, the powder with the target particle size is obtained by screening, and the powder is in a spherical shape.

[0080] Another aspect of the present invention provides an additively manufactured part, which is manufactured using the additive manufacturing method of a nickel-based high-temperature alloy for additive manufacturing provided in the third aspect.

[0081] In a specific embodiment of the present invention, the density of the additively manufactured part is ≥99.2%, preferably ≥99.7%.

[0082] The density of the additively manufactured parts of the present invention in the printed state can reach 99.2%, 99.5%, 99.7%, 99.75%, 99.8%, 99.85%, 99.9%, etc. If further hot isostatic pressing treatment is performed, the density is further improved and can reach more than 99.95%.

[0083] In a specific embodiment of the present invention, the room temperature tensile strength of the additively manufactured part is ≥1340 MPa, preferably ≥1400 MPa; the room temperature elongation after break is ≥9%, preferably ≥11.2%.

[0084] For example, in different embodiments, the room temperature tensile strength of the additively manufactured parts can be 1340MPa, 1360MPa, 1380MPa, 1400MPa, 1420MPa, 1450MPa, 1460MPa, 1470MPa, 1473.3MPa or a range consisting of any two thereof; the room temperature elongation after break can be 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.3%, 14.6% or a range consisting of any two thereof.

[0085] In a specific embodiment of the present invention, the tensile strength of the additively manufactured part at 1100° C. is ≥180 MPa, preferably ≥199 MPa, and the elongation after break at 1100° C. is ≥7%, preferably ≥9%.

[0086] For example, in different embodiments, the tensile strength of the additively manufactured part at 1100°C can be 180MPa, 185MPa, 190MPa, 195MPa, 200MPa, 205MPa, 207MPa, or a range consisting of any two thereof; the elongation after break at 1100°C can be 7%, 8%, 9%, 9.5%, 10.1%, or a range consisting of any two thereof.

[0087] In a specific embodiment of the present invention, the fracture time of the additively manufactured part in a 1000°C / 150MPa high temperature endurance test is ≥17.3h, preferably ≥30h, and the elongation after fracture is ≥7.8%, preferably ≥10.1%. The fracture time of the additively manufactured part in a 1000°C / 150MPa high temperature endurance test can be 17.3h, 20h, 22h, 25h, 28h, 30h, 32h, 33.2h or a range consisting of any two thereof, and the elongation after fracture can be 7.8%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.3% or a range consisting of any two thereof.

[0088] Example 1

[0089] The present embodiment provides a nickel-based high-temperature alloy for additive manufacturing, including the following components in mass percentage: Co21.1%, Cr 8.1%, Al 5.9%, Ti 0.02%, Mo 1.7%, W 3%, Ta 7.1%, Nb 0.5%, Re 1.9%, Si 0.04%, C 0.18%, B 0.005%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0090] A method for preparing a nickel-based high-temperature alloy for additive manufacturing and an additive manufacturing method, comprising the following steps:

[0091] (1) A master alloy ingot was prepared by conventional vacuum induction melting, and a powder was prepared by plasma rotating electrode atomization. Sieving obtained a spherical powder with a particle size of 15 to 53 μm, a D10 range of 26 to 28 μm, a D90 range of 53 to 55 μm, and an oxygen content of ≤100 ppm.

[0092] (2) Using the powder obtained in step (1), a 3D printing sample was prepared by SLM process in an argon atmosphere environment, and the oxygen content in the forming chamber was less than 0.1%; the 3D printing process parameters were: laser power of 275 W, spot diameter of 0.1 mm, scanning speed of 800 mm / s, powder layer thickness of 0.03 mm, and scanning spacing of 0.1 mm.

[0093] Example 2

[0094] This embodiment refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, with the only difference being that the composition of the nickel-based high-temperature alloy for additive manufacturing is different, and the laser power and scanning speed in the 3D printing process are different.

[0095] The nickel-based high-temperature alloy for additive manufacturing of the present embodiment includes the following components in mass percentage: Co20.2%, Cr 7.3%, Al 5.6%, Ti 0.01%, Mo 1.7%, W 2.3%, Ta 6.5%, Nb 0.6%, Re1.2%, Si 0.02%, C 0.15%, B 0.006%, Hf 0.07%, Zr 0.001% and Ni balance and unavoidable impurity elements.

[0096] The laser power in the 3D printing process of this embodiment is 280W and the scanning speed is 850mm / s.

[0097] Example 3

[0098] This embodiment refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, with the only difference being that the composition of the nickel-based high-temperature alloy for additive manufacturing is different, and the laser power and scanning speed in the 3D printing process are different.

[0099] The nickel-based high-temperature alloy for additive manufacturing of the present embodiment includes the following components in mass percentage: Co22.1%, Cr 9.1%, Al 6%, Ti 0.02%, Mo 1.7%, W 3.1%, Ta 7.5%, Nb 0.7%, Re 2.5%, Si 0.04%, C 0.16%, B 0.006%, Hf 0.06%, Zr 0.001% and Ni balance and unavoidable impurity elements.

[0100] The laser power in the 3D printing process of this embodiment is 275W and the scanning speed is 900mm / s.

[0101] Example 4 Group

[0102] The nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 4 refer to Example 1, with the only difference being that in the additive manufacturing method, the laser power and the scanning speed in the 3D printing process parameters are different.

[0103] Example 4a: The laser power is 200 W and the scanning speed is 500 mm / s;

[0104] Embodiment 4b: laser power is 200W, scanning speed is 800mm / s;

[0105] Example 4c: laser power is 200 W, scanning speed is 1100 mm / s;

[0106] Embodiment 4d: laser power is 250W, scanning speed is 500mm / s;

[0107] Embodiment 4e: laser power is 250W, scanning speed is 800mm / s;

[0108] Embodiment 4f: laser power is 250W, scanning speed is 1100mm / s;

[0109] Embodiment 4g: laser power is 300W, scanning speed is 500mm / s;

[0110] Example 4h: laser power is 300 W, scanning speed is 800 mm / s;

[0111] Embodiment 4i: laser power is 300 W, scanning speed is 1100 mm / s;

[0112] Embodiment 4j: laser power is 350W, scanning speed is 500mm / s;

[0113] Embodiment 4k: laser power is 350W, scanning speed is 800mm / s;

[0114] Example 41: The laser power is 350 W and the scanning speed is 1100 mm / s.

[0115] Comparative Example 1

[0116] Comparative Example 1 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0117] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 1 includes the following components in mass percentage: Co10.2%, Cr 6.5%, Al 5.9%, Ti 0.02%, Mo 1.7%, W 3.1%, Ta 7.1%, Nb 0.5%, Re1.9%, Si 0.04%, C 0.17%, B 0.005%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0118] Comparative Example 2

[0119] Comparative Example 2 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0120] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 2 includes the following components in mass percentage: Co21.1%, Cr 8%, Al 5.9%, Ti 0.02%, Mo 1.8%, W 3%, Ta 7.0%, Nb 0.5%, Re 1.8%, Si0.05%, C 0.05%, B 0.006%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0121] Comparative Example 3

[0122] Comparative Example 3 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0123] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 3 includes the following components in mass percentage: Co 21%, Cr 8.1%, Al 6.3%, Ti 0.02%, Mo 1.7%, W 3%, Ta 7.1%, Nb 0.5%, Re 1.9%, Si0.05%, C 0.15%, B 0.005%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0124] Comparative Example 4

[0125] Comparative Example 4 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0126] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 4 includes the following components in mass percentage: Co 21%, Cr 8.1%, Al 3.2%, Ti 2.7%, Mo 1.6%, W 3.1%, Ta 7.1%, Nb 0.5%, Re 1.9%, Si0.05%, C 0.16%, B 0.005%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0127] Comparative Example 5

[0128] Comparative Example 5 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0129] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 5 includes the following components in mass percentage: Co21.2%, Cr 8%, Al 5.9%, Ti 0.02%, Mo 1.7%, W 3.1%, Ta 7%, Nb 0.5%, Re 1.9%, Si0.05%, C 0.17%, B 0.005%, Hf 0.3%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0130] Comparative Example 6

[0131] Comparative Example 6 refers to the nickel-based high-temperature alloy for additive manufacturing, the preparation method and the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy for additive manufacturing is different.

[0132] The nickel-based high-temperature alloy for additive manufacturing of Comparative Example 6 includes the following components in mass percentage: Co21.1%, Cr 7.9%, Al 5.9%, Ti 0.02%, Mo 1.6%, W 3.1%, Ta 7.1%, Nb 0.5%, Re3.3%, Si 0.05%, C 0.18%, B 0.005%, Hf 0.1%, Zr 0.002% and Ni balance and unavoidable impurity elements.

[0133] Comparative Example 7

[0134] Comparative Example 7 refers to the additive manufacturing method of Example 1, except that the composition of the nickel-based high-temperature alloy is different.

[0135] The nickel-based high-temperature alloy of Comparative Example 7 is René 142, which includes the following components in mass percentage: Co 12%, Cr 7.0%, Al 6.2%, Mo 1.6%, W 5%, Ta 6.2%, Re 2.8%, Si 0.02%, C 0.12%, B0.015%, Hf 1.5%, Zr 0.01% and Ni balance and inevitable impurities.

[0136] Experimental Example 1

[0137] The printed samples prepared in different embodiments and comparative examples were subjected to metallographic structure observation and density detection. The optical microstructure diagrams of the printed samples of Embodiments 1 to 4 and Comparative Examples 1 to 7 are shown in FIG. Figures 1 to 11, the density test results are shown in Table 1. It can be seen from the figure that the printed samples prepared in Examples 1 to 3 of the present invention are uniform and dense without cracks. The printed samples prepared in Comparative Examples 1 to 6 will produce a large number of cracks. Through the metallographic structure observation and density test of the printed samples in Example 4, it can be seen that the laser power and the scanning speed are the key parameters affecting the formability. For the alloy system of the present invention, when the laser power is higher than 300W, a large number of pores and some cracks will appear. When the laser power is 200W and the scanning speed is higher than 1100mm / s, unfused defects will appear.

[0138] The printed samples prepared in different embodiments and comparative examples were further subjected to room temperature tensile property tests. The test results are shown in Table 1.

[0139] After the printed samples prepared in different embodiments and comparative examples were subjected to solution treatment and aging (1270°C / 2h+AC, 900°C / 16h+AC), high temperature durability tests were performed under the following test conditions: temperature 1000°C, initial loading force 150MPa. Among them, for those with a density lower than 99.0%, no further high temperature tensile and high temperature durability tests were performed.

[0140] Table 1 Test results of samples in different states

[0141]

[0142]

[0143] From the above test results, it can be seen that the present invention improves the printability of the alloy by controlling the types and contents of key alloying elements in the alloy composition, and improves the high temperature stability of γ' and the high temperature performance of the alloy by high Al, low Ti and appropriate amounts of Ta, Nb, Re, etc. Based on the composition of the nickel-based high temperature alloy of the present invention, its additive manufacturing process is further regulated, so that the obtained additive manufacturing parts can be used to manufacture complex structure aircraft engine hot end components and can meet the requirements of aircraft engine hot end components.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nickel-based high-temperature alloy for additive manufacturing, characterized in that: It includes the following components by mass percentage: Co 17.2%~23.4%, Cr 7.2%~10.5%, Al 5.4%~6.1%, Ti 0.01%~0.1%, Mo1.5%~2%, W 2%~4%, Ta 6.1%~8.1%, Nb 0.5%~1%, Re 0.5%~3.1%, Si 0.02%~0.1%, C 0.13%~0.2%, B 0.005%~0.01%, Hf≤0.2%, Zr≤0.01%, and the balance is Ni and unavoidable impurities.

2. The nickel-based high-temperature alloy for additive manufacturing according to claim 1, characterized in that: In the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is ≤6.1%; Preferably, in the nickel-based high-temperature alloy for additive manufacturing, the sum of the mass percentages of Al and Ti is 5.6% to 6.1%.

3. The nickel-based high-temperature alloy for additive manufacturing according to claim 1, characterized in that: In the nickel-based high-temperature alloy for additive manufacturing, the mass percentage of Hf is 0.04% to 0.12%.

4. The nickel-based high-temperature alloy for additive manufacturing according to claim 1, characterized in that: In the nickel-based high-temperature alloy for additive manufacturing, the mass percentage of Zr is 0.001% to 0.01%.

5. The additive manufacturing method of a nickel-based high-temperature alloy for additive manufacturing according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: 3D printing nickel-based high-temperature alloy powder for additive manufacturing under a protective atmosphere; In the 3D printing, the laser power is 250-300W, and the scanning speed is 700-1000mm / s.

6. The additive manufacturing method according to claim 5, characterized in that: The laser power is 270-280W, and the scanning speed is 800-900mm / s.

7. The additive manufacturing method according to claim 5, characterized in that: Having at least one of the following characteristics: (1) In the 3D printing, the spot diameter is 0.08 to 0.12 mm; (2) In the 3D printing, the scanning interval is 0.08 to 0.12 mm; (3) In the 3D printing, the thickness of a single layer of powder is 0.025 to 0.035 mm; (4) The particle size of the nickel-based high-temperature alloy powder for additive manufacturing is 15 to 53 μm.

8. An additively manufactured part, characterized in that: The additive manufacturing method is adopted as claimed in any one of claims 5 to 7.

9. The additively manufactured part according to claim 8, characterized in that: The density of the additively manufactured part is ≥99.7%.

10. The additively manufactured part according to claim 8, characterized in that: The room temperature tensile strength of the additively manufactured part is ≥1340MPa, and the room temperature elongation after break is ≥9%; the 1100°C tensile strength of the additively manufactured part is ≥180MPa, and the 1100°C elongation after break is ≥7%; the fracture time of the additively manufactured part in a 1000°C / 150MPa high temperature endurance test is ≥17.3h, and the elongation after break is ≥7.8%.